SEMANTIC PARALLELISM IN LITERARY TEXTS - E. O‘rinboyeva (Modern American Journals, 2025)
This article initially provides an overview of the term parallelism and its usage in the field. It briefly outlines the types of syntactic parallelism—namely formal (structural) and semantic parallelism—while placing particular emphasis on the phenomenon of semantic parallelism. The study attempts to analyze the various forms of semantic parallelism using linguistic evidence.
Keywords: Literary text, parallelism, syntactic parallelism, semantic parallelism, word combination, simple sentence, compound sentence, microtext, coordinated compound sentence, asyndetic compound sentence, complex sentence.